2015
DOI: 10.1111/eea.12347
|View full text |Cite
|
Sign up to set email alerts
|

Apparency revisited

Abstract: How easy a plant is to find, or its apparency, is thought to shape plant defenses. Recent meta-analyses suggest that the types of plant defenses employed are not well-predicted by apparency, or apparency can be confounded with life history traits like woodiness and stature. Here, we suggest that the searching environments in which plants grow also influence plant apparency and should thus affect investment in plant defense. Specifically, bare, unvegetated environments may result in greater apparency of inhabit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 57 publications
3
40
1
Order By: Relevance
“…We found increases in the background losses of downy birch foliage to insects in natural environments as we moved from small saplings to large saplings and then to mature trees, while the among‐plant variation in herbivory decreased. Both these patterns fit the predictions of the plant apparency hypothesis (Feeny, ; Fowler, ; Strauss et al., ). First, the larger (more apparent) individuals of downy birch suffered higher insect herbivory than was seen in the smaller (less apparent) individuals, presumably due to the higher probabilities of herbivore encounters with larger plants.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…We found increases in the background losses of downy birch foliage to insects in natural environments as we moved from small saplings to large saplings and then to mature trees, while the among‐plant variation in herbivory decreased. Both these patterns fit the predictions of the plant apparency hypothesis (Feeny, ; Fowler, ; Strauss et al., ). First, the larger (more apparent) individuals of downy birch suffered higher insect herbivory than was seen in the smaller (less apparent) individuals, presumably due to the higher probabilities of herbivore encounters with larger plants.…”
Section: Discussionsupporting
confidence: 77%
“…The plant apparency hypothesis also predicts a higher among‐individual variation in insect herbivory in smaller (juvenile) than in larger (mature) plants: many juveniles would avoid damage because they are hidden, but those discovered by herbivores would receive relatively high amounts of damage (Fowler, ; Strauss et al., ). In contrast, the resource allocation theory would not predict that variation in foliar damage among individuals of the same size class would differ between juvenile and mature plants.…”
Section: Introductionmentioning
confidence: 99%
“…A positive value denotes that sand-covered seeds had a lower removal rate than controls, a negative indicates the opposite. Strauss et al (2015), in surveys of California and New Zealand plants, found that leaf damage was more variable in unapparent species; they suggested that the need to defend may be higher in less-well-matched plants. Numbers along the x-axis of panel B denote number of species tested per family.…”
Section: Sand Coating Defense and Apparencymentioning
confidence: 99%
“…While much is known about the composition, development, location, and underlying genetic mechanisms of mucilage production in a few select systems (e.g., Arabidopsis), fewer studies have examined the role of mucilage in ecological interactions in the field (Fuller and Hay 1983, Gutterman and Shem-Tov 1997, Engelbrecht and Garc ıa-Fayos 2012, Yang et al 2013, Engelbrecht et al 2014. By tightly binding a protective coating of substrate to the seed surface when dried, mucilage-bound substrate may create either a physical barrier to seeds or provide seed camouflage by reducing their visual or olfactory apparency (sensu Fuller and Hay 1983, Strauss and Cacho 2013, Strauss et al 2015. Many seeds are consumed by predators and any defensive functions of seed mucilage have only been tested in a small number of species.…”
Section: Introductionmentioning
confidence: 99%
“…How easily a host plant is found by herbivores, i.e. its apparency (Strauss et al 2015), has been described as a key mechanism driving AR (Castagneyrol et al 2013). Both visual (Dulaurent et al 2012;Damien et al 2016) and chemical (Zhang and Schlyter 2004;Jactel et al 2011) cues used by insect herbivores to locate and colonize a host tree can be disrupted by the presence of heterospecific neighbours.…”
Section: Introductionmentioning
confidence: 99%